Effects of thermal processing combined with sucrose on the vitamin C content, total phenolic content, antioxidant activity, and sensory characteristics of arazá (Eugenia stipitata McVaugh) purée during frozen storage (2015)
The effects of a 80°C, 1 minute thermal treatment (H treatment) and of the same treatment combined with sucrose (SH treatment) on the chemical and sensory qualities of arazá purée were evaluated during 4 months of storage at -20°C. For the control, an untreated sample (C) was included. The chemical qualities evaluated were vitamin C content, total phenolic compounds (TPC), and antioxidant activity (AoA), which were measured with the ferric reducing ability of plasma (FRAP), 2,2'-azinobis( 3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and 1,1-diphenyl-2-picrylhydrazyl (DPPH), while a trained panel was used for the sensory quality evaluation. After 4 months of frozen storage, SH was more effective than H at controlling the loss of chemical quality. SH provided a similar FRAP-AoA (89%) and vitamin C content (87%), as well as a higher TPC (145%), ABTS-AoA (272%), and DPPH-AoA (115%), when compared to C before frozen storage. The total sensory qualities in both the SH purée (15±1) and the H purée (16±1) after 4 months at -20°C were comparable to those of the C purée before the frozen storage (18±2). Therefore, using sucrose combined with a thermal treatment and subsequent frozen storage preserves the chemical and sensory qualities of arazá purée.